Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3892/ol.2017.6986
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate inhibits proliferation and invasion of mouse hemangioendothelioma cells in?vitro and of tumor growth in?vivo

Abstract: Abstract. Artesunate has been demonstrated to be a novel potential antitumor agent in numerous studies. However, its efficacy in infantile hemangioma is unknown. The aim of the present study was to investigate the role of artesunate in the control of vascular tumor biological behavior and molecular mechanism using mouse hemangioendothelioma endothelial (EOMA) cells and a nude mouse model. Cell viability, apoptosis and invasion were determined by an MTT assay, flow cytometric analysis and Transwell invasion ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Several studies on non-urological tumor entities have also demonstrated growth inhibition after ART application. In hemangioendothelioma cells, ART time-and dose-dependently reduced tumor cell growth, concomitantly decreasing the expression of VEGF-A, VEGFR1, VEGFR2, and HIF-1α [46]. Thus, it has been postulated that ART may hold promise in treating vascular tumors, of which RCC is a member.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies on non-urological tumor entities have also demonstrated growth inhibition after ART application. In hemangioendothelioma cells, ART time-and dose-dependently reduced tumor cell growth, concomitantly decreasing the expression of VEGF-A, VEGFR1, VEGFR2, and HIF-1α [46]. Thus, it has been postulated that ART may hold promise in treating vascular tumors, of which RCC is a member.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been postulated that ART may hold promise in treating vascular tumors, of which RCC is a member. Moreover, significant growth inhibition was observed in a mouse model of hemangioendothelioma carcinoma cells following ART treatment, with significantly reduced tumor size [46]. In different gastric cancer cell lines, ART exposure has also resulted in a significant growth reduction [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrated that treatment of compound 20a significantly reduced the mRNA expression levels of VEGFR2 as revealed by quantitative PCR (Figure ). This indicates a significant anticancer potential of compound 20a (Figure ).…”
mentioning
confidence: 82%
“…Therefore, it is urgent to search for complementary therapeutic approaches to increase its effectiveness. Artesunate (ART) is a semi-synthetic derivative of artemisinin and has better anti-tumor activity than artemisinin via reducing the expression of angiogenic proteins [ 114 , 115 ]. Previous studies indicated that ART synergized with TKI sorafenib to induce ferroptosis in hepatocellular carcinoma and enhanced the anti-tumor effect of the TKI sorafenib [ 116 , 117 ].…”
Section: The Roles Of Ferroptosis In the Treatment Of Pca And Rccmentioning
confidence: 99%